Penerapan Data Mining dengan Algoritma C.45 Dalam Memprediksi Penjualan Tempe - Yusuf Maulana; Riki Winanjaya; Fitri Rizki (Bulletin of Computer Science Research, 2022)
Many people talk about business, benefits of business and the many different types of businesses that definitely have one purpose, financial profit or profit. With so many types of business as well as the benefits that can be taken from business, often we definitely feel we feel quickly to pave in the world of business to get profit or more specifically is income. One example of business is selling tempe. Sales is the activity of selling a product or service that needs business authorities or business acknowledgments of a kind of business selling tempe at mandiri ac. In selling of course we have a very many collection of sales information why we should be able to digest the sales information to become new data. In this issue the c4.5 algorithm is a procedure that can help digest or predicate the value of sales at the time to arrive. This research was tested in order to help sellers to predict the sales of their merchantability so that they can prepare or stock materials which is predicted to face an increase in their sales at the time of getting the information between supplied information. From this research can be conclusioned if using the c4.5 algorithm the sales of tempe can be predicted with a quite high accuracy